Estimación de la heredabilidad del intervalo de partos en bovinos cruzados - Vergara G, Oscar; Ceron M, Mario; Hurtado L, Naudin [UNESP]; Arboleda Z, Elkin; Granada P, Juan; Rua B, Clara (Univ Cordoba, 2008)
Objetive. To estimate the heritability of interval calving in crossbred cattle. Materials and methods. Information from database of La Leyenda farm, in the municipality of Caucasia (Antioquia) was used. A single-trait animal model was used, that included genetic group, year of birth, season of birth and the number of calvings as fixed effects and the additive direct genetic, permanent environmental and residual as random effects. Results. The heritability estimated was 0.15 +/- 0.07 and the phenotypic mean was 544 +/- 97 days. Conclusions. The heritability for the interval between calvings was low, indicating that little genetic progress can be achieved by selecting for this characteristic.
Estimation of heritability of calving interval in crossbred cattle
Keywords: Beef cattle; reproduction; calving; bovines